An Analysis of Locutionary, Illocutionary, and Perlocutionary Acts in The Phantom of The Opera - Pribadi, Kayla Zahra Prawoto; Muhammad Hasbi (Bahasa Inggris Program Sarjana Terapan, Universitas Negeri Makassar, 2025)
This research explores the employment of speech acts in The Phantom of the Opera by Gaston Leroux, including locutionary, illocutionary, and perlocutionary acts. Using speech act theory, which was proposed by J.L. Austin and further elaborated on by John Searle, the study looks at how language goes beyond its literal interpretation to convey purpose and elicit reactions within the narrative. A qualitative descriptive methodology is utilized to examine particular dialogues and interactions, unveiling the depths of significance in the characters' speech. The results show how the Phantom's words reveal his intricate feelings, Christine's reactions emphasize her inner struggle, and the story increases tension and compassion in the readers. This study emphasizes the significance of speech acts in reinforcing the novel's central themes of love, fear, and obsession by examining how they express intention, provoke reactions, and influence character relationships.